Floristic variation of tree communities in two distinct habitats within a Forest Park in Pahang, Peninsular Malaysia (Variasi flora bagi komuniti pokok di dua habitat berbeza dalam suatu Taman Rimba di Pahang, Semenanjung Malaysia - Nizam, M.S; Rohani, S; Wan Juliana, W.A (Universiti Kebangsaan Malaysia, 2012)
A study was conducted at Kenong Forest Park, Kuala Lipis, Pahang, to determine species composition and floristic variation of tree communities in two distinct habitats. Two plots of one hectare each were established adjacent to a limestone cave (BK) and in a lowland area (TR) of the forest park. A total of 2091 tree individuals with diameter at breast height (dbh) of 5.0 cm and above were enumerated in both plots where 1091 trees and 1000 trees occurred in the plots BK and TR, respectively. Floristic composition of tree communities at BK plot comprised of 45 families, 110 genera and 199 species, whilst the TR plot contained 232 tree species and 133 genera from 50 families. Altogether, combination of both plots produced floristic composition of 322 species, 161 genera and 54 families. Euphorbiaceae was the most speciose family for both plots, represented by 30 and 27 species in BK and TR plots, respectively. The most dominant species in the BK plot was Streblus ilicifolius (Moraceae) with Importance Value Index (IVi) of 19.18%, whilst in the TR plot, Intsia palembanica (Leguminosae) was the most dominant species with IVi of 14.58%. Total tree basal area for BK and TR plots was 26.91 m2/ha and 29.23 m2/ha, respectively, with Leguminosae dominated basal area in both plots. The Shannon-Weiner diversity Index (H’) of tree communities in both plots show high diversity values where the BK plot indicates H’ value of 4.42 (H’max= 5.26) while the TR plot shows H’ value of 4.79 (Hmax= 5.44), of which the values were different significantly (P<0.05). Community similarity between the two plots was moderate with Sorenson Similarity Index for species composition showed a value of 0.48 (48%). The ordination diagram constructed using Detrended Correspondence Analysis (DCA) demonstrated floristic variation between the two study plots. The DCA obviously separated plots between sites and this indicated a gradient of species change from the BK to the TR sites